THE MENACE OF HEPATITIS B AND C ARE WE RESPONSIBLE FOR IT? - Alam, Intikhab (Journal of Postgraduate Medical Institute, 2011)
The whole world is facing the peril of Chronic Viral Hepatitis that has emerged as an immense public health problem over the past two or three decades. Amongst them, Hepatitis B and hepatitis C viruses (HBV & HCV) have a significant global impact. HBsAg was discovered by 1 Blumberg and his colleagues in 1963 while in 1967 Dane and co-workers discovered viral like 2 particles which carried HBsAg on their surface . Today there are more than 2 billion individuals with serological evidence of hepatitis B infection worldwide. Of these, 400 million are chronic 3,4 carriers and 0.5 to 1.2 million will die annually from cirrhosis and hepatocellular carcinoma